Federalism and fiscal adjustment - May, Ronald James (Oxford : Clarendon P., 1969)
This book deals with the nature of federalism and determine the bargaining capabilities of government
Based on thesis, University of Oxford.
Bibliographical footnotes.
oo 24/01/2019
Loans
Keywords: Intergovernmental fiscal relations; Federal government